Factors Affecting Voluntary Auditor Switching In LQ45 Companies Listed In Indonesia Stock Exchange - Handoko, Bambang Leo; Reneta, Maria; Andrian, Tommy (International Journal of Psychosocial Rehabilitation, 2020)
Aim of this research is to examine the effect of financial distress, audit opinion, audit delay, and changes in percentage of ROA on switching auditors of LQ 45 companies listed in Indonesia Stock Exchange in 2016-2018. Secondary data is sourced from financial statements, published by Capital Market on the Indonesia Stock Exchange. The type of research used in this study is testing hypotheses, using purposive sampling method. There are 54 data samples chosen as research objects. This study uses logistic regression analysis to test the hypothesis. The results showed that of financial distress, audit opinion, audit delay, and changes in percentage of ROA had no significant effect on the auditor switching with a negative coefficient direction. Simultaneously, financial distress, audit opinion, audit delay, and changes in percentage of ROA had no significant effect.